Differences in the expression of the cardiopulmonary alterations associated with anti-immunoglobulin E-induced or active anaphylaxis in mast cell-deficient and normal mice. Mast cells are not required for the cardiopulmonary changes associated with certain fatal anaphylactic responses. - Takeishi, T (1991)
We compared the changes in heart rate (HR), pulmonary dynamic compliance (Cdyn), and pulmonary conductance (GL) associated with three different models of anaphylaxis in genetically mast cell-deficient WBB6F1-W/Wv and congenic normal (+/+) mice. Intravenous infusion of a monoclonal rat anti-mouse IgE produced a marked tachycardia, diminutions in Cdyn and GL, and death in +/+ but not W/Wv mice, and +/+ mice sensitized to develop high circulating levels of IgE exhibited HR, Cdyn, and GL responses to rat anti-IgE challenge which were significantly less intense than those in nonimmunized +/+ mice. By contrast, virtually identical cardiopulmonary responses were observed in either +/+ or W/Wv mice challenged to elicit pure active anaphylactic responses or simultaneous active and anti-IgE-dependent anaphylaxis. These findings show that anaphylactic responses associated with significant tachycardia, reductions in Cdyn and GL, and death can occur in the virtual absence of tissue mast cells. This is true even though, in normal mice, such responses are associated with extensive degranulation of tissue mast cells. By contrast, certain models of anaphylaxis, such as that induced in nonsensitized mice by anti-mouse IgE, can not be elicited in the absence of mast cells.